Indonesia’s Role in International Advocacy for Palestine: Diplomatic Efforts and Challenges in the United Nations (Palestine Issues on Indonesian Society, 2024)
This paper examines Indonesia’s diplomatic efforts to advocate for Palestinian statehood in international forums, particularly within the United Nations (UN). As one of the largest Muslim-majority countries with a history of anti-colonial resistance, Indonesia has consistently positioned itself as a strong supporter of Palestine. The study analyzes Indonesia’s engagement in UN debates, resolutions, and initiatives aimed at advancing Palestinian sovereignty, while also navigating the complexities of global politics. The paper explores the challenges Indonesia faces in balancing its domestic interests—such as national identity and regional influence—with international pressures, particularly from Western powers and Israel. By examining key diplomatic moments, including Indonesia’s role in the UN General Assembly and Security Council, this paper assesses the effectiveness of Indonesia’s advocacy and the limitations it faces in the current geopolitical context. Additionally, the paper highlights how Indonesia’s foreign policy toward Palestine has been shaped by historical, religious, and geopolitical factors, underscoring the complexity of its position in international diplomacy.